Guided by Microbes: Applying Community Coalescence Principles for Predictive Microbiome Engineering - Jennifer D. Rocca (American Society for Microbiology, 2021)
Every seed germinating in soils, wastewater treatment, and stream confluence exemplify microbial community coalescence—the blending of previously isolated communities. Here, we present theoretical and experimental knowledge on how separated microbial communities mix, with particular focus on managed ecosystems.